2018
DOI: 10.21608/ejhm.2018.9121
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Short-term Changes in Left Ventricular Function in Children Undergoing Percutaneous Closure of Patent Ductus Arteriosus by Echocardiography and Tissue Doppler

Abstract: Background: Patent ductus arteriosus accounts for 5-10% of all congenital heart diseases. Left-to-right shunting through the PDA results in pulmonary over-circulation and left heart volume overload. Transcatheter closure is the method of choice for PDA closure when suitable. Some previous studies have described an immediate deterioration of left ventricular functions after percutaneous closure of PDA, which is reversible and improves after few months. Purpose: This study aimed to determine the immediate and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…8,29,30 In addition to monitoring for complications, some studies also assessed changes in LVF parameters and body weight, but most monitoring was not done for a full year after closure. 11,14,31,32 We monitored both LVF parameters and nutritional status, according to the WHO or CDC growth charts depending on patient age. 15 A Nigeria study reported that 92% of CHD patients had malnutrition and 90% of those had severe malnutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,29,30 In addition to monitoring for complications, some studies also assessed changes in LVF parameters and body weight, but most monitoring was not done for a full year after closure. 11,14,31,32 We monitored both LVF parameters and nutritional status, according to the WHO or CDC growth charts depending on patient age. 15 A Nigeria study reported that 92% of CHD patients had malnutrition and 90% of those had severe malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies usually only assessed changes in LVF parameters or nutritional status, not both. 11,14,32 The weakness of our study was the small sample size, due to the large number of patients excluded due to patient non-compliance to clinic visits for evaluation of LVF parameters, as well as incomplete medical record nutritional status data. As such, further study is needed with a larger sample size, and assessment of other possible confounding variables to better elucidate relationships between variables.…”
Section: Resultsmentioning
confidence: 99%